From Policy to Practice: Co-producing Welfare in Elderly Nutrition Assistance at the Frontline - Imam Alfi; Kuswantoro Kuswantoro; Aan Herdiana; Teguh Wiyono; Rina Sangadah; Shodiq Khalidy (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2025)
This study examines how the well-being of older adults is produced through the implementation of nutrition assistance policies at the frontline level. Building on a critique of evaluative approaches that emphasize procedural effectiveness and program outcomes, this research positions nutrition assistance as a welfare practice shaped through everyday interactions among caregivers, families, and older adults. Employing an interpretive qualitative approach and a street-level bureaucracy framework, the study explores how discretion, negotiation, and collaborative work at the household level influence the implementation and interpretation of policies. Data were collected through in-depth interviews, field observations, and field notes involving actors directly engaged in the distribution and reception of assistance. The analysis reveals that policy implementation does not occur as a one-way flow from the state to beneficiaries but rather as a co-productive process involving non-state actors who interpret and adapt formal regulations to the concrete conditions of older adults. Consequently, well-being in this context is understood not only as material sufficiency but also as a relational experience encompassing care, recognition, and support in everyday life. These findings confirm that the meaning and quality of older adults' well-being are shaped in frontline interaction spaces where policies intersect with the social realities of older adults. This study contributes to welfare studies by offering an interpretive perspective that views implementation as a key arena for welfare production and highlights the importance of co-production in social services for vulnerable groups. Keywords: Street-level bureaucracy, co-production, elderly welfare, nutritional assistance.   Penelitian ini mengkaji bagaimana kesejahteraan lanjut usia diproduksi melalui implementasi kebijakan bantuan gizi pada level garis depan (frontline). Berangkat dari kritik terhadap pendekatan evaluatif yang cenderung menekankan efektivitas prosedural dan capaian program, studi ini memposisikan bantuan gizi sebagai praktik kesejahteraan yang dibentuk melalui interaksi sehari-hari antara pendamping, keluarga, dan lanjut usia. Dengan menggunakan pendekatan kualitatif interpretatif dan kerangka street-level bureaucracy, penelitian ini menelusuri bagaimana diskresi, negosiasi, dan kerja kolaboratif di tingkat rumah tangga memengaruhi proses implementasi sekaligus pemaknaan kebijakan. Pengumpulan data dilakukan melalui wawancara mendalam, observasi lapangan, serta catatan lapangan yang melibatkan aktor-aktor yang terlibat langsung dalam proses distribusi dan penerimaan bantuan. Hasil analisis menunjukkan bahwa implementasi kebijakan tidak berlangsung sebagai alur satu arah dari negara kepada penerima manfaat, melainkan sebagai proses koproduktif yang melibatkan aktor non-negara dalam menafsirkan dan menyesuaikan regulasi formal dengan kondisi konkret lanjut usia. Dalam konteks ini, kesejahteraan tidak semata-mata dipahami sebagai kecukupan material, tetapi juga sebagai pengalaman relasional yang mencakup aspek perawatan, pengakuan, dan dukungan dalam kehidupan sehari-hari. Temuan ini menegaskan bahwa makna dan kualitas kesejahteraan lanjut usia dibentuk dalam ruang-ruang interaksi di level garis depan, tempat kebijakan beririsan secara langsung dengan realitas sosial lanjut usia. Studi ini berkontribusi pada kajian kesejahteraan dengan menawarkan perspektif interpretatif yang memandang implementasi kebijakan sebagai arena kunci dalam produksi kesejahteraan, sekaligus menekankan pentingnya koproduksi dalam penyelenggaraan layanan sosial bagi kelompok rentan. Kata kunci: Birokrasi tingkat akar rumput, koproduksi layanan sosial, kesejahteraan lanjut usia, bantuan gizi